Meningkatkan Kreativitas dan Kolaborasi: Hasil Program Seni Pertunjukan PGMI Tahun 2025 - Salsabilla; Dinda Hardianti; Nur Asiyah; Gustiorini; Nurul Suhadah; Rhesti Laila Ulfa; Ika Panggih Wahyuningtyas; Firtsly Mardhatillah (Jurnal Pengabdian Masyarakat Waradin, 2025)
This community service activity aims to empower students and elementary school children through a collaborative performing arts program themed "Earth, Our Home. " The activity is organized by the Study Program of Madrasah Ibtidaiyah Teacher Education (PGMI) at UIN Sulthan Thaha Saifuddin Jambi and the Mamba’ul Ulum Islamic Institute Jambi. The methods of activity include participatory planning, direct assistance in the arts, and cultural performances such as traditional dance, educational drama, musical poetry presentations, and an environmentally friendly fashion show. The results of the activity demonstrate a significant improvement in the students' leadership, collaboration, and communication skills. Meanwhile, elementary school students demonstrate an increased sense of self-confidence and appreciation for local culture as well as environmental issues. This activity successfully strengthened the relationships between institutions and reinforced character education through a culturally relevant approach.